Asian Citrus Psyllid, Diaphorina citri Kuwayama (Insecta: Hemiptera: Psyllidae) - Frank W. Mead; Thomas R. Fasulo (EDIS, 2010)
Revised! EENY-033, an 8-page illustrated fact sheet by F.W. Mead and T. R. Fasulo, is part of the Featured Creatures collection. It describes this serious pest of citrus which is a vector for citrus greening disease or Huanglongbing — identification, distribution, description, life history, damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, July 2010.